A recombinant vaccinia virus based ELISPOT assay detects high frequencies of Pol-specific CD8 T cells in HIV-1-positive individuals. - Larsson, M; Jin, X; Ramratnam, B; Ogg, G; Engelmayer, J; Demoitie, M; Mcmichael, A; Cox, W; Steinman, R; Nixon, D; Bhardwaj, N (1999)
OBJECTIVES: HIV-1-specific CD8 T cells are considered to be critical in anti-HIV responses. It is important to quantify these cells and to determine their antigenic targets. Here quantification of interferon (IFN)-gamma secreting, virus-specific cells was achieved with an enzyme linked immuno spot (ELISPOT) assay. METHODS: Peripheral blood mononuclear cells (PBMC) were infected with recombinant vaccinia vectors expressing HIV-1 genes (gag, pol, env or nef) and added to wells precoated with anti-IFN-gamma monoclonal antibodies. Spot forming cells (SFC), i.e. antigen-specific T cells were detected 24 h later by the addition of biotinylated anti-IFN-gamma monoclonal antibodies, followed by avidin-bound biotinylated horseradish peroxidase. RESULTS: In a cohort of 19 patients, of whom 15 were on highly active antiretroviral therapy, 18 had primed T cells directed against one or more HIV-1 antigens (P < 0.0001). Pol-specific T cells routinely dominated the CD8 response with frequencies up to 2000 SFC per 10(6) PBMC. In HLA A*0201-positive patients, the vaccinia vectors detected much higher frequencies of SFC than haplotype-restricted peptides. Elimination of CD8 T cells resulted in > 90% loss of antigen-specific SFC when vaccinia virus was used as a vector. The number of CD8 SFC exceeded the number of memory cells detected in limiting dilution assays by > 1 log10, whereas a correlation was found between the frequency of effector cells detected by both ELISPOT and MHC class I peptide tetramer assays. CONCLUSIONS: Vaccinia virus vectors used in ELISPOT assays are useful for determining the frequency and specificity of CD8 T cells for individual HIV-1 gene products. The dominance of cytolytic T lymphocytes (CTL) recognizing pol proteins suggests that this antigen should be considered in vaccine strategies.